Biliary Ascariasis: Case Report - Aliulytė, Rūta; Kavaliauskaitė, Agnė; Venskutonis, Donatas (Lietuvos chirurgija, 2022)
Biliary ascariasis is a pathology caused by roundworms when parasites migrate from the jejunum into the bile ducts manifesting in typical clinical symptoms. Ascaris’ eggs mature in the soil, because of that ascariasis is mostly prevalent in tropical and subtropical regions due to poor hygiene, lack of clean drinking water, the consumption of contaminated food. Diagnosis of biliary ascariasis consists of blood and faecal examination, imaging tests, such as ultrasound, magnetic resonance imaging and endoscopic retrograde cholangiography. In this article, we present the case of a patient with biliary ascariasis, review of the epidemiology, life cycle, causes of the migration into the bile duct, clinical manifestations, diagnostic methods and treatment options.
Keywords: ascariasis; bile ducts; endoscopic retrograde cholangiography